Genetic evidence that Celsr3 and Celsr2, together with Fzd3, regulate forebrain wiring in a Vangl-independent manner - Qu, Yibo (National Academy of Sciences, 2014)
Celsr3 and Fzd3, members of “core planar cell polarity” (PCP) genes, were shown previously to control forebrain axon guidance and wiring by acting in axons and/or guidepost cells. Here, we show that Celsr2 acts redundantly with Celsr3, and that their combined mutation mimics that of Fzd3. The phenotypes generated upon inactivation of Fzd3 in different forebrain compartments are similar to those in conditional Celsr2-3 mutants, indicating that Fzd3 and Celsr2-3 act in the same population of cells. Inactivation of Celsr2-3 or Fzd3 in thalamus does not affect forebrain wiring, and joint inactivation in cortex and thalamus adds little to cortical inactivation alone in terms of thalamocortical projections. On the other hand, joint inactivation perturbs strongly the formation of the barrel field, which is unaffected upon single cortical or thalamic inactivation, indicating a role for interactions between thalamic axons and cortical neurons in cortical arealization. Unexpectedly, forebrain wiring is normal in mice defective in Vangl1 and Vangl2, showing that, contrary to epithelial PCP, axon guidance can be Vangl independent in some contexts. Our results suggest that Celsr2-3 and Fzd3 regulate axonal navigation in the forebrain by using mechanisms different from classical epithelial PCP, and require interacting partners other than Vangl1-2 that remain to be identified.